2018
DOI: 10.3390/ijms19030810
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to Plant Pathogens: Theory and Experimental Evidence

Abstract: The two major mechanisms of plant defense against pathogens are resistance (the host’s ability to limit pathogen multiplication) and tolerance (the host’s ability to reduce the effect of infection on its fitness regardless of the level of pathogen multiplication). There is abundant literature on virtually every aspect of plant resistance to pathogens. Although tolerance to plant pathogens is comparatively less understood, studies on this plant defense strategy have led to major insights into its evolution, mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
76
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(80 citation statements)
references
References 111 publications
(182 reference statements)
2
76
2
Order By: Relevance
“…Therefore we propose that the Ma response to PVY C -to infection could be another documented case of tolerance to virus infection. Plant tolerance to pathogens has been recently re-evaluated as "a mitigation of the impact of virus infection irrespective of the pathogen load" 58,60,61 or, in other words, the ability to sustain a significant virus load without any severe effect, on plant growth, yield or reproduction 58 . Indeed results of our time-course analysis clearly showed that Ma plants supported the accumulation of viral RNA to high levels at 14 dpi without showing severe disease symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore we propose that the Ma response to PVY C -to infection could be another documented case of tolerance to virus infection. Plant tolerance to pathogens has been recently re-evaluated as "a mitigation of the impact of virus infection irrespective of the pathogen load" 58,60,61 or, in other words, the ability to sustain a significant virus load without any severe effect, on plant growth, yield or reproduction 58 . Indeed results of our time-course analysis clearly showed that Ma plants supported the accumulation of viral RNA to high levels at 14 dpi without showing severe disease symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Tolerance to biotic stresses caused by pathogens, including viruses, is well-documented in plants ( Rausher , 2001 ; Pagan and Garcia-Arenal, 2018 ). Tolerance has been defined as a mitigation of the impact of virus infection irrespective of the pathogen load ( Cooper and Jones, 1983 ).…”
Section: Introductionmentioning
confidence: 99%
“…In agricultural settings, tolerance is often effective against a larger spectrum of isolates compared to resistance ( Korbecka-Glinka et al, 2017 ). Because viruses are allowed to persist, the selection pressure for emergence of virulent strains is also reduced in tolerant cultivars compared to resistant cultivars ( Rausher, 2001 ; Pagan and Garcia-Arenal, 2018 ). Thus, tolerance can be considered as an evolutionary stable defense response.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that compensation for damage caused by herbivory or pathogen infection could consist of several factors. These include increased chlorophyll concentrations, increased nutrient uptake, increased use of stored resources, delayed flowering and senescence, increased size or number of tissues such as leaves, modified phytohormone balance and altered resource allocation patterns between roots and shoots, or between growth and reproduction (Koch et al, 2016;Mitchell et al, 2016;Pagán & García-Arenal, 2018;Peterson et al, 2017;Strauss & Agrawal, 1999;Tiffin, 2000). In S. nigrum, herbivory was shown to lead to down-regulation of the hormone system and a subsequent increase in root allocation, which may favor competition with other plants following herbivory (Schmidt & Baldwin, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The study of tolerance to pests and pathogens is complicated by the difficulty of defining and quantifying tolerance (Peterson et al, 2017;Stowe et al, 2000). For example, while tolerance to infection by pathogens has been identified in a number of study species and crops (Kover & Schaal, 2002;Parker, Welham, Paveley, Foulkes, & Scott, 2004;Politowski & Browning, 1978;Simms & Triplett, 1994; see also review by Pagán & García-Arenal, 2018), the definitions used for tolerance to infection are often inconsistent (Bingham & Newton, 2009;Castro & Simón, 2016).…”
Section: Introductionmentioning
confidence: 99%